(untitled) (Norwalk, Connecticut, 1993)
This text deals with the spectrum of internal medicine, including: cardiology; respiratory diseases; renal diseases; rheumatology; immunology; infectious diseases; gastroenterology; and ocular manifestations of systemic disease.
Keywords: Nội khoa,Internal medicine